RELATIONSHIP BETWEEN WAIST-HIP RATIO AND COGNITIVE FUNCTION AMONG U.S. CHINESE OLDER ADULTS. (11th November 2018) - Hua, Y; Dong, X
Abstract: There is growing literature regarding body fat distribution and cognitive impairment, but the results are not consistent. Waist -to-hip ratio (WHR) measurements has been developed to reflect abdominal obesity, which is more closely related to metabolic complications in Asian populations. This study aims to examine the relationship between WHR and cognitive function among US Chinese older adults. Data were drawn from 3157 population-dwelling Chinese older adults (58.9% female) aged ≥60 years in the PINE Study. Waist and hip circumferences were measured by trained interviewers. Cognitive function was measured by tests of episodic memory, executive function, working memory, and Chinese Mini-Mental State Examination (C-MMSE). A composite global cognitive score was developed using all tests. Linear regression and quantile regression were conducted adjusting for confounders. For women, WHR showed significant negative associations with all cognitive function tests shown as global cognitive function (b=-0.57, SE=0.14, p<0.001), episodic memory test (b=-0.85, SE=0.18, P<0.001), executive function test (b=-0.43, SE=0.17, P<0.01), working memory (b=-0.42, SE=0.18, P<0.5), and C-MMSE test (b=-0.43, SE=0.19, P<0.5). Men with higher WHR showed poorer cognitive function, while the associations were not significant except for executive function test (b=-0.41, SE=0.20, p<0.05). WHR is inversely related to cognitive function in women. Further longitudinal studies are needed to detect the adverse effects of higher WHR with respect to cognitive function.